Justin som bibelteolog - Müller, Mogens (Dansk Teologisk Tidsskrift, 2019)
Justin Martyr (dead ca. 165) is the earliest known Christian author to develop a Biblical theology. At the same time, he is the last one to acknowledge the Old Testament as Scripture. Especially in his Dialogue with the Jew Trypho, but already in the two Apologies Justin quotes Jewish Holy Scripture extensively. He is the first Christian author to refer to the Septuagint legend about the translation of the Pentateuch, which he extends also to include the translation of the other parts of the Old Testament. Justin is not only convinced about the infallibility of Scripture: he also maintains that the Christians are alone competent to know its real meaning because only they possess the Holy Spirit. The article looks upon Justin as a Bible theologian, focusing on what the Old Greek translation, the Septuagint, contributed to the development of his theology. The rendering ‘virgin’ in Isaiah 7,14 became a point of departure for his distinguishing in a series of Old Testament stories between the eternal, invisible God and another god, an ἕτερος θεός, who acted in a figure visible to humans and who was the pre-existent Christ. In his selection of Old Testament texts, Justin seems to have aimed at giving content to the saying in Luke 24,44. Thus, he delivers proof from Scripture for the belief that the promised Messiah must be identified with Jesus. As to the question of how Justin became acquainted with Old Testament Scripture, the article defends the view that it was mainly through independent reading. Thus, he did not use any already existing collections of testimonia. Rather, he created one. To the old question of how Justin could quote the same text in different versions, the preferred answer in this article is that the Dialogue mainly consists of older manuscripts, which Justin had, in an old age, mechanically worked together, not so much in order to convince Jews as to offer a manual for Christians who might be tempted by a Jewish understanding of Scripture.